Slovenski razvoj besedotvornih pomenov pri izglagolskih samostalnikih, posebno pri glagolniku - Žele, Andreja (Slovenski jezik, 1997)
The present paper presents the development of Slovene word-formation theory, the various distributional criteria of complex words, and research which is today based on the cause-effect relationship between syntax and word-formation theory.
Keywords: besedotvorje; linguistics; lingvistika; samostalnik; Slovene; slovenščina; word formation